Global Burden of Leptospirosis: Estimated in Terms of Disability Adjusted Life Years. - Paul R Torgerson; José E Hagan; Federico Costa; Juan Calcagno; Michael Kane; Martha S Martinez-Silveira; Marga G A Goris; Claudia Stein; Albert I Ko; Bernadette Abela-Ridder (PLoS Neglected Tropical Diseases)
Background Leptospirosis, a spirochaetal zoonosis, occurs in diverse epidemiological settings and affects vulnerable populations, such as rural subsistence farmers and urban slum dwellers. Although leptospirosis can cause life-threatening disease, there is no global burden of disease estimate in terms of Disability Adjusted Life Years (DALYs) available. Methodology/principal findings We utilised the results of a parallel publication that reported global estimates of morbidity and mortality due to leptospirosis. We estimated Years of Life Lost (YLLs) from age and gender stratified mortality rates. Years of Life with Disability (YLDs) were developed from a simple disease model indicating likely sequelae. DALYs were estimated from the sum of YLLs and YLDs. The study suggested that globally approximately 2.90 million DALYs are lost per annum (UIs 1.25-4.54 million) from the approximately annual 1.03 million cases reported previously. Males are predominantly affected with an estimated 2.33 million DALYs (UIs 0.98-3.69) or approximately 80% of the total burden. For comparison, this is over 70% of the global burden of cholera estimated by GBD 2010. Tropical regions of South and South-east Asia, Western Pacific, Central and South America, and Africa had the highest estimated leptospirosis disease burden. Conclusions/significance Leptospirosis imparts a significant health burden worldwide, which approach or exceed those encountered for a number of other zoonotic and neglected tropical diseases. The study findings indicate that highest burden estimates occur in resource-poor tropical countries, which include regions of Africa where the burden of leptospirosis has been under-appreciated and possibly misallocated to other febrile illnesses such as malaria.